2006
DOI: 10.1007/s00439-006-0288-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the oxidative stress pathway and susceptibility to non-Hodgkin lymphoma

Abstract: Oxidative damage caused by reactive oxygen species (ROS) and other free radicals is involved in a number of pathological conditions including cancer. In a population-based case-control study of non-Hodgkin lymphoma (NHL) (n = 518 cases, 597 controls) among women in Connecticut, we analyzed one or more single nucleotide polymorphisms (SNPs) in ten candidate genes (AKR1A1, AKR1C1, AKR1C3, CYBA, GPX1, MPO, NOS2A, NOS3, OGG1, and SOD2) that mediate oxidative stress directly or indirectly in the NADPH oxidase-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…Statistically significant differences in DLBCL and FL were shown for T/T homozygotes only. By contrast, Lan et al (13) found no difference between patients and healthy blood donors regarding this polymorphism in a study of 161 DLBCL and 119 FL patients. Smedby et al (11) suggested that polymorphic variation in the XRCC3 gene, but not in the ERCC2 and XRCC1 genes, may be essential in the pathogenesis of FL.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Statistically significant differences in DLBCL and FL were shown for T/T homozygotes only. By contrast, Lan et al (13) found no difference between patients and healthy blood donors regarding this polymorphism in a study of 161 DLBCL and 119 FL patients. Smedby et al (11) suggested that polymorphic variation in the XRCC3 gene, but not in the ERCC2 and XRCC1 genes, may be essential in the pathogenesis of FL.…”
Section: Discussionmentioning
confidence: 87%
“…Specifically, Wang et al (12) observed that the rs2297518 Leu/Leu variation in nitric oxide synthase (NOS) NOS2A results in a 3.4-fold increased risk of diffuse large B-cell lymphoma (DLBCL) and a 2.6-fold increased risk of FL. By contrast, Lan et al (13), who evaluated SNPs in oxidative stress genes including NOS2A in another population, did not detect any statistically significant associations between analyzed SNPs and risk of NHL, with the exception of SNPs in AKR1A1 and CYBA (13). Recently, a pooled analysis of SNPs in 27 gene regions involved in DNA repair based on three studies of almost 2,000 cases and 1,800 controls was published by Shen et al (14).…”
Section: Introductionmentioning
confidence: 99%
“…An increased lymphoma risk was attributed to the frequent genetic polymorphism 242C>T in the CYBA subunit of NAD(P)H oxidase in one study (26), but not in another (27). Moreover, 242C>T in CYBA and another genetic polymorphism in NCF4 were associated with chronic doxorubicin-induced cardiomyopathy (28).…”
Section: Introductionmentioning
confidence: 92%
“…The few studies on the rs7195830 polymorphism have not elucidated the mechanisms underlying this result, but this polymorphism was also selected as an oxidative stress-related locus in several previous studies on non-Hodgkin lymphoma and cervical cancer. 13,14 It is possible that the rs7195830 polymorphism, which is located in the 3¢-untranslated region, might influence messenger RNA stability or modulate the transcription rate and affect reactive oxygen species generation. Further investigations on the function of this polymorphism are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, rs7195830 has been mentioned in studies on non-Hodgkin lymphoma and cervical cancer as an oxidative stress-related locus. 13,14 Therefore, in the present study, we hypothesized that the rs1049255 and rs7195830 polymorphisms of the CYBA gene are associated with arterial elasticity indices in a large cohort of apparently healthy Chinese individuals across a wide age range. As physical activity may influence oxidative stress biomarkers, 15 we further explored whether physical activity could modify the genetic effect.…”
Section: Introductionmentioning
confidence: 99%